மலரும் சருகும் நாவலில் நாடார் மக்களின் இனவரைவியல் / Ethnography of Nadar People in the Novel Malarum Sarugum - ஜோ. கிளம்மி ஜெனி பிரியா / J. Clemy Jeni Priya (International Journal of Tamil Language and Literary Studies)
Sangam literature is evidence of the cultural, historical, political, linguistic and ethnographic truth of Tamil society. There are many ethnic groups in the Tamil society from the ancient times. It is possible to know that ancient Tamils lived as ethnic groups. The Nadar ethnic group is considered as a group of that ethnic group. They are an ethnic group living in Tamil Nadu. They live in the ghettos by building their own houses. They eat corn flour dosa and rice, goat meat, pulp, fish, umachi rasam, pork and chicken. Also, they have the habit of putting betel leaves and toddy. Men wear a shirt and dhoti and women wear a saree to cover their body. The Nadars develop their economy by farming as their occupation. They have a habit of marrying after a proper engagement with a young woman. The practice of love marriage is also found among Nadar people. The deity worship of these people can be seen in two types namely Christian worship and Hindu worship. Christians worship the Lord Jesus. Hindu Nadars worship Ayyanar, Kali, Karuppannasamy, Saptakanni, Sudalimadan, Ena Pechi, Sandip Pilliyar and Kulathankarai Pilliyar as their deities. Nadars live as joint families. There is a custom of meeting in the middle of the town to punish the wrongdoer and give justice. They use tools such as Airkutti, Kolhumuna, Pannarival, Shovels etc. for agriculture and Kalaiyam, Bronze Kumba and Aluminum plates for household needs. These people are using weapons like Palai sickle, Velkambu and Panniarival as their weapons. The novel portrays that the high-caste rich men have received money from the government by writing fake accounts in the name of Nadar caste labourers. A promissory note becomes evidence for confirming the payment of money to the wage labourers. The superiors ordered that the labour of the Nadar caste labourers should be measured by a small yardstick in an exploitative manner. Nadars fought against this injustice and won to get their wages properly. This struggle is called the Kalmarakal struggle in Tamil Nadu history. This article explores the ethnographical state of the Nadar community in the novel “Malarum Sarugum”.